2014
DOI: 10.1002/anie.201409336
|View full text |Cite
|
Sign up to set email alerts
|

Krebs Cycle Metabolon: Structural Evidence of Substrate Channeling Revealed by Cross‐Linking and Mass Spectrometry

Abstract: It has been hypothesized that the high metabolic flux in the mitochondria is due to the self-assembly of enzyme supercomplexes (called metabolons) that channel substrates from one enzyme to another, but there has been no experimental confirmation of this structure or the channeling. A structural investigation of enzyme organization within the Krebs cycle metabolon was accomplished by in vivo cross-linking and mass spectrometry. Eight Krebs cycle enzyme components were isolated upon chemical fixation, and inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
104
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(112 citation statements)
references
References 20 publications
3
104
0
Order By: Relevance
“…Another possibility, as mentioned earler, is the generation of artificial metabolons. Recently, several studies have demonstrated the physical assembly of TCA cycle enzymes to form metabolite channels or metabolons (Wu and Minteer 2015;Zhang et al 2017). The sequential enzymes of the metabolic pathway can be associated into a temporary structural-functional complex by non-covalent interactions, anchorage to membranes, and by encapsulation of enzymes in protein-coated microcompartments (Figure 2).…”
Section: Perspectives For Synthetic Biology Approaches At Modifying Tmentioning
confidence: 99%
“…Another possibility, as mentioned earler, is the generation of artificial metabolons. Recently, several studies have demonstrated the physical assembly of TCA cycle enzymes to form metabolite channels or metabolons (Wu and Minteer 2015;Zhang et al 2017). The sequential enzymes of the metabolic pathway can be associated into a temporary structural-functional complex by non-covalent interactions, anchorage to membranes, and by encapsulation of enzymes in protein-coated microcompartments (Figure 2).…”
Section: Perspectives For Synthetic Biology Approaches At Modifying Tmentioning
confidence: 99%
“…However, protein complexes-as an organizational principle-cannot account alone for the complex integration of the many cellular processes in situ. Additional layers of functional organization, beyond free diffusion and random collision of functional biomolecules within organelles, are required to ensure, for example, the efficient transfer of substrates along enzymatic pathways (dubbed metabolons; Srere, 1987;Wu & Minteer, 2015;Wan et al, 2015;Wheeldon et al, 2016), the effective transduction of signals (Wu, 2013), and the synthesis of proteins according to the local cellular needs (Gupta et al, 2016). This requires spatially and temporally synchronized sets of protein complexes-protein communities (Barabasi & Oltvai, 2004;Menche et al, 2015)-which we define as higher-order, often dynamically associated, assemblies of multiple macromolecular complexes that benefit from their close proximity to each other in the cell.…”
Section: Introductionmentioning
confidence: 99%
“…The enzymes that complete the cycle show homology across Bacteria, Archaea, and Eukaryota, and are highly efficient 1,2 ; consequently, there are relatively few known variations of a complete TCA cycle. Many bacteria have incomplete cycles, while some autotrophs use a reverse (reductive) cycle to fix carbon from CO 2 3 .…”
Section: Main Textmentioning
confidence: 99%